The influence of credit factors on the development of the real economic sector in the conditions of economic instability - Abramova, A. S.; Fedyshyn, M.F.; Marich, M.G. (Financial and credit activity: problems of theory and practice, 2018)
The analysis of the status of bank lendingin the reals ectoriscarriedout. The scope of credits for financing of subjects of the real economy are estimated. In order to determine the impact of bank lending on the state of the real economy, the relation ship between the volume of loansprovidedby banks to the country's economy, assets of the banking industry and the main macroeconomic indicator – GDP have been established. The application of economic-mathematical modeling in the study of the banking sector's activity enabled the collection and streamlining of statistical information on the main parameters of the banking system development; using the leastsquaresmethod, to construct a six-factor linear regression model of the in fluence of the factors of the banking system on GDP on a matrixbasis; thecorrelationbetweentheindicatorsofthe NBU discountrate, theexchangerate, inflation, returnonassets and capital of the banking system, the interest rate on loansarei nvestigated. It is determined that thelending of the real economysectorin Ukraineneeds a substantialre think ingin the direction of orientation of banking institution stolends of priority activities in the national economy. The practical application of the calculation senablesto in crease the level of the Nationa lBank's management in order to ensure the efficientfunctioning of bothindividual banking institutions and the banking systemas a wholes in cethefurthergrowth of Ukraine dependson the stable development of the banking system, the possibility of enteringthe international financial market sandactive participation in the globalization processes. A reliable and developed banking sector play sanextremely important rolein stabilizing the country's economy.
Keywords: bank lending real sector gross domestic product bank assets exchange rate discount rate loan rate economic instability.